Pendampingan Ibu Hamil Melalui Layanan Antenatal Care dan Edukasi Pencegahan Stunting Berbasis Pemetaan Risiko Prenatal - Rahmi, Sania Lailatu; Sefrina, Yosi; Mesalina, Rosa; Dariani, Lili (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2025)
Prenatal risk factors associated with stunting can be reduced by monitoring prenatal risk factors with appropriate management. The objective of the Community Service Program (PkM) is to increase the knowledge and awareness of pregnant women regarding prenatal risk factors for stunting so that they can receive appropriate counseling and education. The method used was cross-program collaboration with community health centers and direct involvement in examining pregnant women using the 10T standard. The instrument used was a questionnaire containing 15 questions to measure the success of the education. The results achieved were that 80% of pregnant women received 10T antenatal care services, 96.7% of pregnant women had stunting risk factors, with the mapping of risk factors finding 73.3% had low education, 86.7% had incomes below the minimum wage, 63.3% had risky BMI, 66.7% were anemic, and 56.7% had non-standard antenatal visits. The average knowledge score before assistance was 59, increasing to 77 after assistance, a ±30.5% increase. Further efforts are needed to sustain PkM activities in the form of strengthening the role of cadres and health workers in continuous monitoring.